Pengaruh Keberagaman Dewan terhadap Nilai Perusahaan melalui Kinerja ESG - Nadifah, Rifda; Dahlan, Muhammad; Handoyo, Sofik (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the effect of board characteristics—gender diversity, cultural background, expertise, and experience—on firm value, with Environmental, Social, and Governance (ESG) performance serving as an intervening variable. The research focuses on publicly listed companies across five European Union countries: Germany, France, Italy, Spain, and the Netherlands. Methodology/Approach: A quantitative approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The sample was drawn through purposive sampling, targeting firms that disclosed ESG scores and provided comprehensive data on board composition. Results/Findings: The findings indicate that only gender diversity within boards has a significant and positive effect on ESG performance. Other characteristics—cultural background, expertise, and experience—did not show significant impacts. Additionally, ESG performance itself was not found to have a significant influence on firm value. Similarly, board characteristics did not directly affect firm value in this study. Conclusions: The results suggest that while gender diversity may strengthen ESG-related outcomes, this does not necessarily translate into higher firm value within the observed context. This highlights a gap between ESG initiatives and tangible financial performance. The findings underscore the importance of effective governance practices that integrate ESG into broader corporate strategies rather than relying solely on board diversity. Limitations: This study is limited to five EU countries and a single observation period, restricting the generalizability of the results. Contribution: The study contributes to corporate governance literature by clarifying which board attributes improve ESG performance under EU gender quota regulations and offering insight into why diversity alone may not directly increase firm value.